Fiscal Monitor, October 2013 : Taxing Times. (Fiscal Monitor; Fiscal Monitor ;, 2013)
Persistently high debt ratios in advanced economies and emerging fragilities in the developing world cast clouds on the global fiscal landscape. In advanced economies, with narrowing budget deficits, the average public debt ratio is expected to stabilize in 2013-14-but it will be at a historic peak. At the same time, fiscal vulnerabilities are on the rise in emerging market economies and low-income countries-on the back, in emerging market economies, of heightened financial volatility and downward revisions to potential growth, and in low-income countries, of possible shortfalls in commodity prices and aid. Strengthening fiscal balances and buttressing confidence thus remain at the top of the policy agenda. Against that backdrop, this issue explores whether and how tax reform can help strengthen public finances. Taxation is always a sensitive topic and is now more than ever at the center of policy debates around the world. Can countries tax more, better, more fairly? Results reported in this issue show that the scope to raise more revenue is limited in many advanced economies and, where tax ratios are already high, the bulk of the necessary adjustment will have to fall on spending. In emerging market economies and low-income countries, where the potential for raising revenue is often substantial, improving compliance remains a central challenge.